Current status of bronchoscopic lung volume reduction with endobronchial valves - Shah, Pallav; Herth, Felix (Thorax, 2014)
Introduction Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. Emphysema is a component of COPD characterised by hyperinflation resulting in reduced gas exchange and interference with breathing mechanics. Endoscopic lung volume reduction using one-way valves to induce atelectasis of the hyperinflated lobe has been developed and studied in clinical trials over the last decade. - Methods Searches for appropriate studies were undertaken on PubMed and Clinical Trials Databases using the search terms COPD, emphysema, lung volume reduction and endobronchial valves. - Results The evidence from the randomised clinical trials suggests that complete lobar occlusion in the absence of collateral ventilation or where there is an intact lobar fissure are the key predictors for clinical success. Other indicators are greater heterogeneity in disease distribution between upper and lower lobes. The proportion of patients that respond to treatment improves from 20% in the unselected population to 75% with appropriate patient selection. The safety profile for endobronchial valves in this severely affected group of patients with emphysema was acceptable and the main adverse events observed were an excess of pneumothoraces. - Conclusion Selected patients have the potential of significant benefit in terms of lung function, exercise capacity and possibly even survival. These considerations are essential in-order to maximise patient benefit in a resource-limited environment and also to ensure that beneficial treatments are available for the appropriate patient.